CHARACTER BASED LIFELONG EDUCATION - Maisah, Maisah (Reflective, 2012)
Lifelong education can happened in home, schools, and in the community. Lifelong education has the same value with education seen by Muhammad, because according to Muhammad, everyone learn from they were born and never stop until they die.